Knowledge Transfer from Universities to Industry Through University Technology Transfer Offices - Asad Abbas; Anders Avdic; Kathryn Chang Barker; Peng Xiaobao (Видавничий дім "Академперіодика" НАН України, 2018)
Introduction. This paper focuses on knowledge generation and the way in which it is transferred from universities to
industry. Most well reputed universities have several departments and university-run enterprises that engage in research.
The purpose of these research units is to help universities provide breakthrough innovation through the generation of new
knowledge.
Problem Statement. For this we chose to study China's University Technology Transfer Offices (UTTOs) to gather
concrete evidence of university knowledge generation for commercial use in industry. The objective of this study is get indepth
information about the role of UTTOs in the transfer of such knowledge.
Purpose. The generation of new knowledge contributes to the field of science and technology; in turn, industry can use
this knowledge to produce new innovative products or improve existing ones. This study aims to identify the process of
knowledge transfer from universities to industry in China.
Materials and Methods. Our study was carried out as a qualitative case study in the Anhui province of China. Data
was mainly collected through semi-structured interviews with technology transfer experts working in technology transfer
offices. Collected data were analyzed using a knowledge transfer model with six phases: 1) awareness, 2) acquisition,
3) transformation, 4) association, 5) application, and 6) feedback.
Results. In China, universities and their research groups dominate in the generation and commercialization of research
results, with UTTOs acting as technology bridges between the two parties, as well as providing legal and business
services.
Conclusions. This paper contributes by offering a detailed description of the knowledge transfer process and specifically
the role and activities of UTTOs. This research also helps Chinese and international researchers currently carrying out
research on the technology transfer process in China. Вступ. Висвітлено питання генерації знань та способу їх передачі від університетів у промисловість. Найвідоміші
університети мають кілька департаментів та підприємств, які займаються дослідженнями. Мета цих підрозділів
полягає в тому, щоб допомогти університетам забезпечити інноваційні рішення шляхом створення нових знань.
Проблематика. Генерація нових знань сприяє розвитку галузі науки та техніки, які, у свою чергу, використовуються промисловістю для виробництва нових інноваційних продуктів або вдосконалення вже існуючих. На прикладі
роботи департаментів трансферу технологій (ДТТ) в університетах Китаю вивчено роботу та зібрано конкретні
факти генерації знань для комерційного використання в промисловості.
Мета. Отримання детальної інформації про роль ДТТ у передачі знань від університетів до промисловості
в Китаї.
Матеріали та методи. Дослідження проведено в китайській провінції Аньхой (Аньхуей). Збір даних виконували
за допомогою напівструктурованих інтерв’ю з фахівцями з передачі технологій, які працюють в офісах департаментів
передачі технологій. В подальшому їх аналізували за допомогою моделі передачі знань, яка передбачає шість етапів:
поінформованість, придбання, перетворення, зв’язок ідей, застосування та зворотній зв’язок.
Результати. Університети Китаю та їх дослідницькі групи домінують у виробництві та комерціалізації результатів досліджень, а ДТТ відіграють роль технологічних мостів між двома сторонами, а також надають юридичні та
бізнес-послуги.
Висновки. Стаття містить детальний опис процесу передачі знань та, зокрема, висвітлює роль та діяльність ДТТ
Китаю, що може бути корисним китайським та міжнародним науковцям у проведенні досліджень процесу передачі
технологій. Введение. Раскрыто вопрос генерации знаний и способа их передачи от университетов в промышленность. Самые известные университеты имеют несколько департаментов и предприятий, которые занимаются исследованиями.
Цель этих подразделений лежит в том, чтобы помочь университетам обеспечить инновационные решения путем создания новых знаний.
Проблематика. Генерация новых знаний способствует развитию отрасли науки и техники, которые, в свою очередь, используются промышленностью для производства новых инновационных продуктов или усовершенствования уже существующих. На примере работы департаментов трансфера технологий (ДТТ) в университетах
Китая изучено работу и собрано конкретные факты генерации знаний для коммерческого использования в промышленности.
Цель. Получение детальной информации о роли ДТТ в передаче знаний от университетов к промышленности
в Китае.
Материалы и методы. Исследование проведено в китайской провинции Аньхой (Аньхуей). Сбор данных производили с помощью полуструктурированных интервью специалистов с передачи технологий, которые работают в
офисах департаментов передачи технологий. В дальнейшем их анализировали с помощью модели передачи знаний,
которая предусматривает шесть этапов: информированность, получение, преобразование, связь идей, использование
и обратная связь.
Результаты. Университеты Китая и их исследовательские группы доминируют в производстве и коммерциализации результатов исследований, а ДДТ играют роль технологических мостов между двумя сторонами, а также предлагают юридические и бизнес-услуги.
Выводы. Статья содержит детальное описание процесса передачи знаний и, в частности, раскрывает роль и деятельность ДТТ Китая, что может быть полезным китайским и международным ученым при проведении исследований процесса передачи технологий.